KELAYAKAN ASPEK MATERI DAN MEDIA DALAM PENGEMBANGAN BUKU AJAR SASTRA LAMA - Wulandari, Yosi; Purwanto, Wachid Eko (Universitas PGRI Sumatera Barat, 2017)
This study aims to produce teaching materials in the form of textbooks in the Old Literature courses through analysis of the structure and meaning of ancient Minangkabau manuscripts. This research is a development research. The research and development model adapted from Borg & Gall. The research begins by conducting (1) preliminary studies to search for research findings related to the condition of old literary materials as developed products. (2) Develop a product based on research findings, that is analyzing the structure and meaning of ancient Minangkabau manuscripts. (3) Conduct field test of the product, which is the old literary material developed from structural analysis and the meaning of ancient manuscripts minangkabau. (4) Make revisions to correct weaknesses in the field test phase. The result of the research data is the percentage of the validity of the validation and responses obtained from the test of material experts, media experts, and individual testing by the students. The result of the textbook validation from the test subject can be concluded very feasible and very valid used in the old literature course.